The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1088/0957-4484/20/44/445709
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology effects on polarization switching in nanoscale ferroelectrics

Abstract: The effects of surface morphology on polarization switching in thin ferroelectric films are investigated using a real-space, time-dependent Ginzburg-Landau model that incorporates electrostatic interactions. We consider a two-dimensional uni-axial ferroelectric film with a thickness that varies sinusoidally. Polarization switching, starting from a single domain remnant state, is simulated for several surface modulation amplitudes and wavelengths. We demonstrate that surface heterogeneities produce inhomogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…3c,d) which indicate that the height variation of the BFO/SRO film is considerably smaller than that for the BFO/LMSO film. Since domain wall pinning is more likely to occur for the film with larger surface roughness3839, these topography images suggest that the BFO/LSMO film has a higher density of stronger pinning sites.…”
Section: Resultsmentioning
confidence: 95%
“…3c,d) which indicate that the height variation of the BFO/SRO film is considerably smaller than that for the BFO/LMSO film. Since domain wall pinning is more likely to occur for the film with larger surface roughness3839, these topography images suggest that the BFO/LSMO film has a higher density of stronger pinning sites.…”
Section: Resultsmentioning
confidence: 95%
“…When a potential difference is applied across such films, the nonplanar surface morphology results in an inhomogeneous distribution of the electric field within the material. Recently, it has been shown that such electric field inhomogeneity can significantly reduce the applied electric field required to initiate polarization switching process in ferroelectric thin films . In this work, we investigate the influence of such inhomogeneous electric fields on the piezoresponse of such films using experimental measurements, finite element modeling, and phase field simulations.…”
Section: Piezoelectric Response Resultsmentioning
confidence: 99%
“…The phase field method has emerged as a powerful technique to simulate ferroelectric domains and polarization switching . Recently, this method was used to simulate the polarization switching behavior in thin films with a nonplanar morphology . We use this framework here to understand the enhancement of piezoresponse due to the nonplanar surface.…”
Section: Piezoelectric Response Resultsmentioning
confidence: 99%
“…This barrier is reduced to ~0.35 eV once the surface contains steps. The surface roughness effectively reduces the barriers for domain nucleation at free surfaces driven by external electric fields, as that shown in ferroelectrics 30 . We also calculate the barrier for kink propagation inside twin boundaries.…”
Section: Resultsmentioning
confidence: 75%